Towards the creation of a school identity through heritage. A case study at IES San Isidro of Madrid - Gómez-Redondo, Carmen; Gómez-Redondo, María José; Fontal Merillas, Olaia (Pulso. Revista de educación, 2019)
IES San Isidro de Madrid is a historical high school that, for some years, has been developing a revitalization social project of the center through its own heritage. This work aims to describe and analyze the process of creating its own museum in the high school and the identity inertias of the community associated with this process. To this end, research work has been designed based on the case study method. High school publications and the informant interviews were the focus of the data collection and analysis process. The main results suggest that the construction of a museum inside the centre has helped to create interpretation communities where not only members of the school community participate, but also other kind of educational agents, such as graduate students, university students, residents of the nearby area, etc. In addition, the museum becomes a metaphor of the community’s creative process and its relationship with its heritage, and evolves in the same way the community does.
Keywords: Heritage Education; Community of Interpretation; Identization